Effect Of Variable Amplitude Loading On Fatigue Characteristic And Failure Probability For Automobile Steering Knuckle - Ad Suhadak, Fadrah Hanim (2019)
Steering knuckle is an important compartment in a vehicle. It functions as a joint connecting the suspension and steering system where the steering arm could maneuver the automobile direction. While driving, the automobile steering knuckle is exposed to variable amplitude loading that is influenced by the conditions of the road surfaces. Traditionally, most of the fatigue life assessment is performed using constant amplitude loading. However, in operation most of the engineering components are subjected to stresses which varies with time. Therefore, the study of fatigue life under variable amplitude loadings is an important subject. The main objective of this study is to investigate the fatigue life behavior and fatigue failure probability based on the variable amplitude loading. In this study, the actual variable amplitude loadings are obtained from steering knuckle of 1300 cc national automobile. The fatigue strain signals, which acts as a variable amplitude loading are captured using a 2 mm strain gauge and a data acquisition system while the vehicle is driven onto different road surfaces. The fatigue strain signal sample is recorded for 60 seconds. Four types of road are used in this study which are the residential area road, rural road, country road and highway road. The fatigue strain signal behaviors are then determined using global statistical analysis. Prior to capturing the fatigue strain signals, the position of the strain gauge on automobile steering knuckle is determined using finite element analysis. For simulation purposes, the automobile steering knuckle is modeled using a 3D scanner, Faro Laser Scan Arm to provide an accurate dimension. Then, the finite element model is created using a commercial finite element software. The model is meshed using tetrahedral element type. Loadings are applied on strut mount and lower ball joint with consideration of the weight of the car with passenger and driven at constant speed. The fatigue damage behavior of automobile steering knuckle is simulated using Glyphwork® software. The obtained fatigue damaged is correlated with the fatigue strain signal behavior. Then, the fatigue failure probability that contributed from the different road surface condition is determined. Results indicated that the fatigue strain signals behavior, fatigue damage, fatigue life of automobile steering knuckle are influenced significantly by the different type of road surfaces profile. Residential road recorded the highest strain signal range, vibration energy and power content of steering knuckle. It also contributed to the most damage as compared to the rural, country and highway road on automobile steering knuckle. The failure probability that is in consideration of different type of road surfaces also contributed to the prediction of fatigue life. Morrow approach recorded a higher fatigue life of steering knuckle than SWT approach and it is found that Morrow approach is more suitable to be applied in steering knuckle case. This is due to the type of loading condition and material used in steering knuckle which is more suitable for Morrow approach.